RECONSTRUCTION OF UNDERSTANDING OF HOLINESS BASED ON 1 PETER 1:14-16 AND ITS RELEVANCE FOR TEACHERS IN FORMING THE CHARACTER OF CHRISTIAN YOUTH - candra daeli; Stenly R. Paparan (Fakultas Filsafat Universitas Advent Indonesia, 2026)
The rapid advancement of digital technology and social change has profoundly impacted today's young Christians' moral and spiritual lives, evident in declining values, identity crises, and a serious gap between profession and practice. This demands robust character grounded in biblical truths and a comprehensive understanding of holiness. This article seeks to reconstruct and deepen the concept of holiness from 1 Peter 1:14-16 and to examine its practical relevance for Christian Religious Education (PAK) teachers in shaping adolescent character. By employing a qualitative descriptive approach and theological exposition of scriptural, theological, and academic literature, this study explores holiness comprehensively. The findings indicate that holiness in this passage is not merely a moral demand or legalistic rule, but a divine calling to share in God's holy nature, realized through continuous sanctification by the Holy Spirit. Thus, holiness is understood not only as a normative concept, but as an essential transformative life practice that forms spiritually mature adolescents firmly rooted in Christian values.